Evaluation of BiomeFert Biofertilizer for Growth and Yield Improvement in Glycine max L. Varieties Dega-1 - Fatimah, Fatimah; Putri, Elsha Nadya Marchelia; Salsabila, Syarifah; Rahayuningtyas, Nazil Dwi; Soelistyo, Anastasya Nabila Putri; Arneni, Wanda Dya; Febrionny, Princessa Nandita; Supriyanto, Agus; Nimatuzahroh, Nimatuzahroh; Geraldi, Almando (AGRIVITA Journal of Agricultural Science, 2025)
Biofertilizer application can potentially reduce chemical residues in soil from synthetic fertilizers. This study investigates the effects of varying doses and application frequencies of biofertilizers on the growth, productivity, and Relative Agronomic Effectiveness (RAE) of Glycine max L. A Completely Randomized Design was employed, with 9 treatment combinations and 2 control groups (positive and negative), each replicated three times. The biofertilizer doses tested were 5, 10, and 15 ml per plant (B5, B10, B15), and application frequencies included 1 week after planting (WAP) (F1), at 1 and 4 WAP (F2), and at 1, 4, and 8 WAP (F3). The negative control received no biofertilizer, while the positive control received NPK (5 g/plant). Plant growth was assessed by measuring height and leaf number, and productivity was evaluated based on the number of pods, pod weight, dry seed weight, and weight per 100 seeds. Data were analyzed using one-way ANOVA. The results indicated that the treatment with 10 ml of biofertilizer applied twice (B10F2) significantly improved the growth and productivity of Glycine max L., achieving an RAE value of 169.70%.